2015
DOI: 10.1038/ncomms7345
|View full text |Cite
|
Sign up to set email alerts
|

TMC-1 attenuates C. elegans development and sexual behaviour in a chemically defined food environment

Abstract: Although diet affects growth and behaviour, the adaptive mechanisms that coordinate these processes in non-optimal food sources are unclear. Here we show that the C. elegans tmc-1 channel, which is homologous to the mammalian tmc deafness genes, attenuates development and inhibits sexual behaviour in non-optimal food, the synthetic CeMM medium. In CeMM medium, signalling from the pharyngeal MC neurons and body wall muscles slows larval development. However, in the non-standard diet, mutation in tmc-1 accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 69 publications
(74 reference statements)
5
47
1
Order By: Relevance
“…The finding that we can detect alkali-activated currents in ADL and ADF soma rather than their sensory endings suggests that TMC-1 is indeed functionally expressed in these neurons but probably not dedicated to detecting alkaline pH in the environment. This is also consistent with the notion that TMC-1 may have other functions (Zhang et al, 2015). Future effort is needed to determine the physiological roles of TMC-1 in these neurons.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The finding that we can detect alkali-activated currents in ADL and ADF soma rather than their sensory endings suggests that TMC-1 is indeed functionally expressed in these neurons but probably not dedicated to detecting alkaline pH in the environment. This is also consistent with the notion that TMC-1 may have other functions (Zhang et al, 2015). Future effort is needed to determine the physiological roles of TMC-1 in these neurons.…”
Section: Resultssupporting
confidence: 91%
“…Two TMC family genes, tmc-1 and tmc-2 , are present in C. elegans , of which tmc-1 has been suggested to encode a Na + -sensitive channel required for salt chemosensation and dietary signaling (Chatzigeorgiou et al, 2013; Zhang et al, 2015). We have characterized tmc-1 gene in the current study, and found that it is required for worms to sense noxious alkaline environment mediated by the ASH nociceptive neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Neuromodulators are involved in metabolic homeostasis and energy regulation in both mammals and Drosophila (Loftus et al 2000;Leibel et al 1995;Obici et al 2002;Harris-Warrick & Marder 1991;Pfaff et al 2008). We asked, therefore, whether manipulation of neuromodulatory circuits might affect respiration in a nutritional status-dependent manner (Zhang et al 2015). Flies were either allowed to feed ad libitum or were starved for 24 h prior to warm-induced Kir2.1 expression.…”
Section: Silencing Aminergic Circuits Affects Co2 Production During Dmentioning
confidence: 99%
“…It is the first multicellular organism to have its genome completely sequenced (C. elegans Sequencing Consortium, 1998), which facilitates bioinformatics analysis. Besides, its genetic tractability, ease of handling and maintenance also make C. elegans become a powerful model system to study development, neurobiology and stress responses (Brenner, 1974;Corsi et al, 2015;Zhang et al 2015b;Hunt, 2016). Only two studies were performed to study pH response in C. elegans.…”
Section: Introductionmentioning
confidence: 99%